Reduced cingulate gyrus volume in Cavalier King Charles Spaniels with syringomyelia and neuropathic pain revealed by voxel-based morphometry: a pilot study - Nitzsche, Björn; Schulze, Sabine; Boltze, Johannes; Schmidt, Martin J. (Frontiers in Neuroanatomy, 2023)
Objective Pathomorphological alterations of the central nervous system in dogs, such as syringomyelia and Chiari-like malformation, can cause cranial and cervical hyperesthesia and neuropathic pain. The long-term activity of the pain network can induce functional alteration and eventually even morphological changes in the pain network. This may happen especially in the prefrontal and cingulate cortex, where atrophy of the gray matter (GM) was observed in humans with chronic pain, irrespective of the nature of the pain syndrome. We tested the hypothesis that Cavalier King Charles Spaniels (CKCS) with Chiari-like malformation and associated syringomyelia (SM) and pain show cerebral morphological differences compared to animals without signs of syringomyelia and pain. Methods Volumetric datasets of 28 different brain structures were analyzed in a retrospective manner, including voxel-based morphometry, using magnetic resonance imaging data obtained from 41 dogs. Results Volumetric analyses revealed a decrease in GM volumes in the cingulate gyrus (CG) in CKCS with SM and chronic pain when normalized to brain volume. This finding was supported by voxel-based morphometry, which showed a cluster of significance within the CG. Conclusion GM atrophy in the CG is associated with chronic pain and thus may serve as an objective readout parameter for the diagnosis or treatment of canine pain syndromes.